Domestic Violence in Lay People's Perception - Madyaningrum, Monica E. (ANIMA Indonesian Psychological Journal, 2010)
The purpose of the study was to document lay people’s perception on domestic violence as reflect- ed through their comments on a poster specifically designed for this study. The poster contained images and messages, which were targeted to prevent and stop domestic violence. The study in- volved two groups of men and women from two neighborhoods located in the inner city of Sura- baya. Data collection was taken by using focus group discussion, which was analyzed, by using thematic analysis. The findings showed that domestic violence was still perceived mainly as a pri- vate or personal problem, which therefore require private or personal intervention. The findings were discussed using socio-cultural perspective on domestic violence. Penelitian ini ingin melihat bagaimana masyarakat awam melihat dan memaknai persoalan kekera- san dalam rumah tangga (KDRT) yang terjadi di sekitarnya sebagaimana terefleksikan melalui komentar mereka pada poster yang didesain khusus untuk penelitian ini. Poster tersebut berisi gambar dan pesan yang bertemakan pencegahan dan penanganan KDRT. Penelitian ini dilakukan pada kelompok laki-laki dan perempuan di dua kampung di tengah kota Surabaya. Pengumpulan data dilakukan dengan metode diskusi kelompok terarah dan data diolah menggunakan analisis tematik. Hasil penelitian menunjukkan bahwa KDRT masih dipandang sebagai kasus domestik yaitu urusan internal rumah tangga ketika penyebab serta solusinya bersumber pada aspek internal keluarga. Temuan ini kemudian didiskusikan dalam kaitannya dengan tinjauan sosio-kultural terhadap persoalan KDRT.